Damage morphology of C/C-SiC composites under impact tests - Srivastava V.K. (My University, 2025)
C/C-SiC composite is a fibre composite made of carbon fibre and a brittle ceramic matrix. This has the advantage to combine monolithic ceramic with a higher tolerance of damage and lower specific stress. Characteristically states of defects already arise during the production process, such as crack pattern, fable fibres / matrix bond, delamination and high porosity. Some of the defects are favoured in view of the damage tolerance necessary for the technical use, but make it difficult to evaluate the damage condition. The main advantage of carbon fibre reinforced silicon carbide (C/C-SiC) is the damage tolerant mechanical behaviour compared to monolithic ceramics. Fracture mechanics test were carried out on chevron notched bend specimens. The present study is aimed to qualitatively examine the damage surface of C/C-SiC composites by the use of Scanning Electron Microscope (SEM) with the change of impact load. For quality assurance reasons the development of micro crack pattern under different loading conditions was investigated. Low and high impact tests were performed on C/C-SiC composites before and after the conditioning at 1600°C temperature.